Antimicrobial Susceptibility Profile and Extended-Spectrum Beta-Lactamase Phenotype of E. coli Isolated From Poultry - Matilda Ayim-Akonor; Rita Ohene Larbi; Doreen Dela Owusu-Ntumy; Benjamin Kissi Sasu; Hilda Emefa Ohene Asa; Theophilus Odoom (International Journal of Microbiology, 2025)
Bacterial resistance to antibiotics is increasing globally, with the food-animal sector (FAS) playing a key role. Knowledge of the antimicrobial resistance (AMR) of microbes from the FAS is important in the development of country-specific methods to minimize the AMR burden. In Ghana, there is limited data on the susceptibility of FAS bacteria to frequently used antimicrobials. We evaluated the susceptibility of 58 Escherichia coli isolates obtained from chickens to nine antibiotics and further assessed their potential to produce extended-spectrum beta-lactamase (ESBL). The Kirby–Bauer disc diffusion and combined disc methods were used following the Clinical and Laboratory Standards Institute guidelines. Nearly all isolates showed high resistance (> 50%) to all the antibiotics except gentamicin, to which more than two-thirds (n=48, 83%) were susceptible. Resistance to streptomycin, tetracycline, and ampicillin was observed to be 93%, 97%, and 100%, respectively. All isolates were multidrug resistant. Over one-third of the isolates (n=22, 37.9%) were resistant to seven classes of antibiotics, and a substantial proportion (n=12, 20.7%) exhibited resistance to all eight antimicrobial classes. None of the isolates was detected as an ESBL producer. Most farms (86%) did not have a footbath, and the majority (71%) changed the bedding material after 4 weeks. Free-range chickens were kept on 80% of the farms. The high resistance to frequently used antibiotics suggests long-term use of these antimicrobials, which may be attributed to poor biosecurity practices that may be exposing the birds to frequent infections. There is a need to educate farmers on the prudent use of antibiotics and adherence to good biosecurity practices.